Crystal structure of donepezil hydrochloride form III, C24H29NO3⋅HCl. Issue 4 (December 2021) - Reid, Joel W.; Kaduk, James A.
Abstract : The crystal structure of donepezil hydrochloride, form III, has been solved with FOX using laboratory powder diffraction data previously submitted to and published in the Powder Diffraction File. Rietveld refinement with GSAS yielded monoclinic lattice parameters of a = 14.3662(9) Å, b = 11.8384(6) Å, c = 13.5572(7) Å, and β = 107.7560(26)° (C24 H30 ClNO3, Z = 4, space group P 21 / c ). The Rietveld-refined structure was compared to a density functional theory (DFT)-optimized structure, and the structures exhibit excellent agreement. Layers of donepezil molecules parallel to the (101) planes are maintained by columns of chloride anions along the b -axis, where each chloride anion hydrogen bonds to three donepezil molecules each.